Progressive Muscle Relaxation in Families With Psychosocial Health Problems - Mad Zaini; Intan Isnaini Agustina; Dian Dwi Cahya Ningrum (Jurnal Kesehatan, 2022)
Psychosocial health problems in a family could arise as a result of the condition of family member(s) who is sick. This condition can cause increased emotional stress in the family. One of the efforts that can be done due to the condition is to increase the family's ability to control the stress experienced. This study aims to determine the effect of Progressive Muscle Relaxation therapy on families with psychosocial health problems. This study is a quasi-experimental design with a pre-test post-test without control group design, which was conducted from January to February 2022. A total of 40 respondents were taken using total sampling. The data was analyzed using bivariate data analysis (paired t-test). The result of the study showed that Progressive Muscle Relaxation has an effect on reducing anxiety as psychosocial health problems in families.